CANTATAdb: A Collection of Plant Long Non-Coding RNAs - Szcześniak, Michał W. (Plant Cell Physiol, 2016)
Long non-coding RNAs (lncRNAs) represent a class of potent regulators of gene expression that are found in a wide array of eukaryotes; however, our knowledge about these molecules in plants is still very limited. In particular, a number of model plant species still lack comprehensive data sets of lncRNAs and their annotations, and very little is known about their biological roles. To meet these shortcomings, we created an online database of lncRNAs in 10 model plant species. The lncRNAs were identified computationally using dozens of publicly available RNA sequencing (RNA-Seq) libraries. Expression values, coding potential, sequence alignments as well as other types of data provide annotation for the identified lncRNAs. In order to better characterize them, we investigated their potential roles in splicing modulation and deregulation of microRNA functions. The data are freely available for searching, browsing and downloading from an online database called CANTATAdb (http://cantata.amu.edu.pl, http://yeti.amu.edu.pl/CANTATA/).